International Islamic Youth Education: Character Development and Intercultural Competence in World Muslim Scout Jamboree 2025 - Mohammad Muslih; Syarifah Syarifah; Riza Ashari; Saiful Anwar; Harisman H (Jurnal Penelitian Pendidikan, 2026)
This research explores the role of the World Muslim Scout Jamboree 2025 as a platform for International Islamic Youth Education, focusing on character development and intercultural competence among Muslim youth. Employing a qualitative case study design, data were collected through participant observation, semi-structured interviews, and document analysis involving student delegates, international participants, scout leaders, and organizing committee members. The findings indicate that participation in the jamboree significantly strengthened moral responsibility, leadership disposition, and collaborative skills through experiential learning processes. Moreover, intensive intercultural interaction fostered adaptive communication skills, cultural awareness, and sensitivity toward diversity. The shared religious identity among participants functioned as a facilitating bridge for intercultural dialogue while allowing the preservation of distinct national cultures. The study also reveals the emergence of a reflective International Muslim youth identity characterized by moderation, inclusivity, and peace-oriented values. These findings suggest that international scouting initiatives can serve as an effective non-formal educational model integrating character education, global citizenship competencies, and Islamic values. The research contributes to the conceptual development of International Islamic Youth Education by demonstrating how global youth engagement programs can bridge local Islamic educational traditions with broader global experiences. Future longitudinal studies are recommended to examine the sustainability of these developmental impacts over time.